Pelatihan Merajut Sebagai Upaya Peningkatan Keterampilan dan Produktivitas Ibu-Ibu dan Remaja di Kota Bengkulu - Lestari, Egi Sri; Nauli, Roma Dona; Vera, Vety (Yayasan Daarul Huda Kruengmane, 2025)
This training aims to improve participants' knitting skills and economic productivity through applicable training based on relevant activities. The approach used is Participatory Action Research (PAR), which actively involves participants in the learning process from problem identification to solution development, with a combination of lectures, demonstrations, and direct practice methods. The results of the study showed that around 90% of participants were able to understand and create knitted works according to the patterns taught, and felt an increase in self-confidence and economic capabilities. High community support and participant interest in developing knitted products as a business opportunity show the potential for developing micro-businesses based on handicrafts in local communities. This activity has proven effective in improving practical skills, opening up new economic opportunities, and strengthening community empowerment in improving welfare in a sustainable manner.